2022
DOI: 10.1038/s41467-022-34129-4
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-associated increases in soluble tau relate to tau aggregation rates and cognitive decline in early Alzheimer’s disease

Abstract: For optimal design of anti-amyloid-β (Aβ) and anti-tau clinical trials, we need to better understand the pathophysiological cascade of Aβ- and tau-related processes. Therefore, we set out to investigate how Aβ and soluble phosphorylated tau (p-tau) relate to the accumulation of tau aggregates assessed with PET and subsequent cognitive decline across the Alzheimer’s disease (AD) continuum. Using human cross-sectional and longitudinal neuroimaging and cognitive assessment data, we show that in early stages of AD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 75 publications
6
45
0
Order By: Relevance
“…Our statical models suggested that the APOEε4-dependent Aβ effects on longitudinal tau deposition were mediated by the concentrations of p-tau217 + . Although this suggest potential causal relationships that are accordance with previously proposed biological models of disease progression 27,38,39 , mechanistic studies are needed to examine this further. Finally, future multicenter studies with longer follow-up intervals and multiple time points are needed to better characterize the temporal relationships between APOEε4, Aβ, and tau across the AD spectrum.…”
Section: Discussionsupporting
confidence: 55%
“…Our statical models suggested that the APOEε4-dependent Aβ effects on longitudinal tau deposition were mediated by the concentrations of p-tau217 + . Although this suggest potential causal relationships that are accordance with previously proposed biological models of disease progression 27,38,39 , mechanistic studies are needed to examine this further. Finally, future multicenter studies with longer follow-up intervals and multiple time points are needed to better characterize the temporal relationships between APOEε4, Aβ, and tau across the AD spectrum.…”
Section: Discussionsupporting
confidence: 55%
“…Microglia consume large amounts of glucose (Xiang et al , 2021 ), hence a TREM2‐related microglial response may result in FDG‐PET hypermetabolism in the earliest stages of Aβ accumulation, where neurodegeneration is typically not yet apparent. In late Aβ accumulators, a TREM2‐related microglial response parallels p‐tau 181 which has been associated with subsequent neurodegeneration (Ossenkoppele et al , 2021 ; Pichet Binette et al , 2022 ). Hence higher sTREM2 may be associated with FDG‐PET hypometabolism in subjects with late‐stage Aβ accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting findings of microglial activation on the development of tau pathology may be explained by several factors, including the use of different animal models of AD, which recapitulate different aspects of AD pathophysiology, or using different markers of tau pathology including soluble and fibrillar forms of tau. CSF p‐tau reflects hyperphosphorylated tau in its soluble form, one of the earliest tau‐related changes in AD that is closely associated with Aβ, preceding the formation of intracellular neurofibrillary tau aggregates (Hansson, 2021 ; Pichet Binette et al , 2022 ). Therefore, microglia may have different effects on p‐tau hyperphosphorylation and aggregation, which will be important to study in greater detail in future studies by combining fluid and PET biomarkers of microglial activation and tau pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases, which is considered to be a kind of terrifying disease threatening human health and social well-being. , The symptoms of AD are characterized by gradual amnestic cognitive impairment accompanied by loss in speech express, visuospatial processing, and execution . The occurrence of cognitive symptoms often lags behind the progression of AD due to the slow and insidious onset of the disease. , However, current treatments cannot reverse the progress of the disease after the onset of cognitive symptoms. , Genetic evidence and biochemical and histopathological observations indicate that various neurotoxic aggregates formed during the aggregation of β-amyloid peptide (Aβ) and amyloid plaques formed by fibril deposition are the main factors for predisposing AD. , Aβ has been broadly regarded as an important biomarker and therapeutic target for AD. , Hence, developing therapeutic strategies by targeting Aβ is an effective pathway for AD treatment.…”
Section: Introductionmentioning
confidence: 99%